Building a Generation of Character: Strategies and Challenges of Character Education at the Elementary School Level in Indonesia - Marhamah, Marhamah; Damanik, Muhd Hayyanul (Yayasan Sembilan Pemuda Indonesia, 2025)
Character education at the elementary school level plays a crucial role in shaping a generation with strong moral values, which serve as the foundation for both individual and societal development. This article reviews various strategies implemented to integrate character education in Indonesian elementary schools, as well as the challenges faced during its implementation. The approach used in this research is a literature review, where the authors analyze and evaluate various academic sources, journals, and related articles discussing the implementation of character education at the elementary school level in Indonesia. One of the main strategies identified is the integration of character values into the national curriculum, such as the 2013 Curriculum and the Merdeka Curriculum. Values such as mutual cooperation, integrity, independence, and responsibility are taught through a project-based approach that allows students to practice these values in real-life situations. Furthermore, habituation and role models provided by teachers are key strategies in educating students, with various routine activities such as flag ceremonies and group prayers helping students develop discipline and cooperation. Strengthening school culture, including norms, customs, and traditions that support character education, is also a crucial pillar in creating an environment conducive to student character development. Although these strategies have shown positive results, challenges such as disparities in educational resources, a lack of teacher training, and the influence of social media remain obstacles to the equitable implementation of character education across Indonesia. This article emphasizes the importance of collaboration between the government, schools, and the community to overcome these challenges and realize effective character education at the elementary school level.